Pola Pendidikan Islam Menurut Syekh Taqiyuddin AnNabhani (Suatau Tinjauan Analisis) - Lidiya Rusadi Siregar (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This research outlines the objectives, curriculum, methods and implementation of Islamic education in an-Nabhani's vision, which rejects secularism and is oriented towards the Khilafah system. The results of the analysis show that an-Nabhani's education pattern is holistic, combining aqidah, tsaqofah, and sharia to form individuals who are ready to apply Islam in a kaffah manner. The relevance for Islamic Religious Education (PAI) in Indonesia is the application of a curriculum based on Islamic values without discrimination, although full implementation requires adaptation to the local context. This research is expected to enrich the discourse on contemporary Islamic education.